The drone mapping of Kampung Paya Rumput Jaya, Melaka - Abdullah, Alias; Ibrahim, Mansor; Hj. Mohd. Noor, Norzailawati; Ibrahim, Illyani; Harun, Nor Zalina; Abdul Latip, Nurul Syala; Abdullah, Ahmad Afiq Aiman; N Murtaza, Fatin Farhana (2020)
This mapping is done using drone at Kampung Paya Rumput Jaya, Melaka. It was conducted to measure the Malay settlement pattern.